1995
DOI: 10.1128/jvi.69.1.430-438.1995
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA modulates the acid sensitivity of foot-and-mouth disease virus capsids

Abstract: Foot-and-mouth disease virus (FMDV) manifests an extreme sensitivity to acid, which is thought to be important for entry of the RNA genome into the cell. We have compared the low-pH-induced disassembly in vitro of virions and natural empty capsids of three subtypes of serotype A FMDV by enzyme-linked immunosorbent assay and sucrose gradient sedimentation analysis. For all three subtypes (A22 Iraq 24/64, A10 61 , and A24 Cruzeiro), the empty capsid was more stable by 0.5 pH unit on average than the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 57 publications
6
58
0
Order By: Relevance
“…It is also possible that empty capsids of the Asia I virus strain that we used were more resistant to acid conditions than those of the O type virus. Curry et al (1995) found that acid-resistance varied among different strains of FMDV within the same serotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that empty capsids of the Asia I virus strain that we used were more resistant to acid conditions than those of the O type virus. Curry et al (1995) found that acid-resistance varied among different strains of FMDV within the same serotype.…”
Section: Discussionmentioning
confidence: 99%
“…It exists in seven serotypes (O, A, C, Asia, SAT1, SAT2 and SAT3), and has the basic picornavirus structure depicted in Figure 1 (terms defined there will be used throughout this paper). FMDV enters cells through receptor-mediated endocytosis followed by acid pH-dependent release and translocation of RNA across the endosomal membrane (Carrillo et al, 1984;Mason et al, 1994;Curry et al, 1995). FMDV can attach to cells via argine-glycine-aspartic acid (RGD)-binding integrin molecules (Surovoi et al, 1988;Fox et al, 1989;Baxt and Becker, 1990;Mason et al, 1994;Berinstein et al, 1995), such as α v β 3 (Berinstein et al, 1995;Jackson et al, 1997;Neff et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, recombinant empty capsids (WT and mutants VP1 N17D and VP1 N17D + VP2 H145Y) were produced in the absence of FMDV RNA by co-expression in BHK-21 cells of the P1-2A capsid precursor and the viral protease 3 C from plasmids pL1-1 and pSKRH-3C, respectively 34 . Previous evidence has unambiguously shown that in recombinant FMDV empty capsids VP0 is fully processed due to an RNA-independent, autocatalytic cleavage of VP0 to render VP4 and VP2 28,30 . In particular, the crystal structure of the empty capsid shows that cleavage and reveals that the empty capsid is virtually identical to the RNA-filled virion, even at atomic resolution, except for the absence of the RNA itself.…”
Section: Resultsmentioning
confidence: 98%
“…In addition to any putative effect of the VP1 N17D substitution on intracapsid interactions, its acid-stabilizing effect could be related also (or instead) to some change in capsid-RNA interactions. Some evidence obtained with FMDV 30,31 and Coxsackie B3 virus 32 indicates that not only capsid proteins determine the stability of these picornaviruses, but also the viral RNA could contribute to determine virion stability or instability at both acidic pH and increased temperature. However, the potential role in virion stability of RNA-capsid interactions had not been explored for these viruses.…”
mentioning
confidence: 99%